Multiwavelength ﬁber laser in four mode ﬁber - Jamaludin, J.; Zakaria, Z.; Awang, N.A. (Elsevier Science Ltd, 2017)
Multiwavelength ﬁber laser is a nonlinear phenomenon that has a great potential for optical communication system. A stable triple-wavelength ﬁber laser in four mode ﬁber had been demonstrated experimentally by employing Sagnac ﬁlter in a simple close loop laser cavity. The Sagnac loop ﬁlter conﬁguration was constructed using a 2 m of polarization maintaining ﬁber (PMF), a 3 dB coupler and a polarization controller. The laser is able to sustain triple-wavelength laser generation at 13.1 dBm output power of Erbium-Doped Fiber Ampliﬁer (EDFA) as all laser wavelengths produced less than 0.25 nm ﬂuctuation for over 20 min of unstoppable lasing operation. This laser conﬁguration also has ﬂexibility to perform single, dual and triple wavelength laser by controlling the EDFA output power.